Optimization of formulation and process of Australian sweet lupin (ASL)-wheat bread - Villarino, Casiana Blanca Jucar; Jayasena, Vijay; Coorey, Ranil; Chakrabarti-Bell, S.; Johnson, Stuart (Elsevier, 2015)
This study aimed to optimise formulation and process factors of Australian sweet lupin (ASL)-refined wheat bread bun to maximise the ASL level whilst maintaining bread quality using response surface methodology (RSM) with a central composite face-centered design. Statistical models were generated that predicted the effects of level of ASL flour incorporation (g/100 g of ASL-wheat composite flour), ASL flour volume weighted mean particle size (mm), water incorporation level (g/100 g ASL-wheat composite flour), mixing time of sponge and dough (min) and baking time (min) on crumb specific volume (CSV), instrumental texture attributes and consumer acceptability of the breads. Verification experiments were used to validate the accuracy of the predictive models. Optimisation of the formulation and process parameters using these models predicted that formulations containing ASL flour at 21.4e27.9 g/100 g of ASL-wheat composite flour with volume weighted mean particle size of 415e687 mm, incorporating water at 59.5e71.0 g/100 g ASL-wheat composite flour, with sponges and dough mixed for 4.0e5.5 min and bread baked for 10e11 min would be within the desirable range of CSV, instrumental hardness and overall consumer acceptability. Verification experiments confirmed that the statistical models accurately predicted the responses.